Relative efficiency in utilization of domestic and imported inputs in the Malaysian manufacturing sector, 1983-2005: The case of resources and non resources based industries - Sulaiman, Noorasiah; Abdul Hamid, Khalid; Abdul Rashid, Zakariah (2011)
The focal point of this study is to examine the efficiency of utilization on intermediate input, particularly in terms of resources and non resources-based industries in the Malaysian manufacturing sector. Since relative efficiency can determine how well an input performed, our main interest rest on whether there exist any discrepancy between the performance of domestic and imported intermediate input. To undertake such analysis, we employ the basic table of input and output matrices derived from various publications of the Malaysian Input-Output Tables, which covers the period of 1983 to 2005. The input-output coefficients of domestic and imported inputs were then simulated by using commodity technology model, notwithstanding the conventional technical coefficient methods. The former method is expected to give a more reasonable result, which is hoped to overcome criticism of the latter. It is anticipated that three main findings might be gained from this study, especially in terms of whether these resources were sourced from either local’s or foreign’s. Firstly, non resources‐based industries have shown that the used of both inputs have a higher percentage of sub-sectors improved. Secondly, resource-based industries show high percentage of productivity improve in imported input used; while domestic input utilization have rather a low percent during the study. Thirdly, the number of industries that is efficient in utilizing imported input more higher, both, in resources and non resources-based industries. Although these imperative findings bring to a close match between the two different inputs, it is clear that imported inputs of resources and non resources-based industries are more productive than domestic inputs.